Can the ceramic industry be a new and hazardous sector for work-related asthma?. (April 2018) - Kurt, Ozlem Kar; Ergun, Dilek; Basaran, Nursen
Abstract: Background: Work-related asthma (WRA) constitutes a significant proportion of all asthma cases and continues to be reported from different industries. The aim of the study was to identify the occupations that can be related to WRA and diagnostic steps used in suspected WRA patients. Methods: We retrospectively reviewed the clinical records of WRA suspected patients who were referred to Ankara Occupational and Environmental Diseases Hospital, Turkey from January 2015 to January 2017. Detailed occupational history, the diagnostic steps such as pulmonary function testing (PFT), peak expiratory flow (PEF) monitoring and nonspecific bronchial provocation tests (NSBPT) were recorded. Results: Among 160 patients, 148 were male and 12 were female. Only 2 of them were diagnosed as work-exacerbated asthma (WEA). Diagnosis of asthma was based on using reversible airflow limitation 28.8% (n = 46) or NSBPT 31.9% (n = 51). Toxicological analysis showed that 28 patients had heavy metal poisoning, 9 patients had solvent poisoning, 4 patients had both. According to occupations, 32 of them were ceramic workers (20.0%) and 27 of them were metal workers (16.9%). Plastic workers (4 ± 2.8 years), cleaners (6.2 ± 5.7 years), metal workers (7.4 ± 5.4 years), painters (10 ± 5.2 years), ceramic workers (10.8 ± 5.9 years) had the shortest exposure durations for development of occupational asthma (OA). An analysis of variance showed that the effect of heavy metal and solvent poisoning on mean time for onset of OA was not significant. Conclusions: The results demonstrate that besides the sectors known to cause WRA, ceramic and metal industries can be related to important exposures related to WRA. Medical surveillance of employees in this sector is important in early detection. Highlights: New workplace exposures causing WRA continue to be reported in different sectors. This is the first study to show different types of occupations especially ceramic workers that can be related to WRA. Workers' processing fields which can contain hazardous exposures in ceramic industry are raw material preparation, forming and shaping.